Educational Management Strategies for Developing Students’ Discipline and Courtesy through Habit Formation and Supervision - Zuhriana Widya Rahayu Ning Tyas; Shifa Fauziah; Alif Alfian Syafa'at; Dinatus Zahro; Akbar Riadus Shabirin; Nur Rohman Hidayat (Journal of Educational Management Research, 2026)
This study aims to examine the development of students’ disciplinary and courteous character at SMA Negeri 1 Jogorogo through consistent habituation practices supported by a structured supervision system. Employing a descriptive qualitative approach, data were collected through observations, semi-structured interviews, and documentation. The research subjects included on-duty teachers, homeroom teachers, guidance and counseling teachers, pre-service teacher interns, and students. The findings reveal that daily habituation activities—such as morning greetings, punctual attendance, uniform and grooming checks, morning literacy sessions, collective prayers, and school assemblies—play a significant role in shaping students’ character. Teacher role modeling emerges as a key factor influencing students’ behavioral development, while the school’s disciplinary system, implemented collaboratively by on-duty teachers, the Student Discipline Enforcement Team (TPDS), and counseling teachers, further reinforces positive habits. Interview results indicate that students perceive these routines as beneficial in fostering responsibility, time management skills, and polite interpersonal communication. The involvement of pre-service teacher interns also strengthens the character-building process due to their communicative and relatable approach. Overall, the study concludes that character formation at the school is effective, supported by strong collaboration among teachers, students, pre-service interns, and institutional commitment. The findings imply